Periodization: What is it good for? - Mattocks, K. T.; Dankel, S. J.; Buckner, S. L.; Jessee, M. B.; Counts, B. R.; Mouser, J. G.; Laurentino, G. C.; Loenneke, J. P. (Journal of Trainology, 2016)
Resistance training increases muscle size and strength and is associated with numerous health benefits. For many, periodization serves as the cornerstone of programming for resistance training and is commonly touted in the literature as a superior method of training. Objective: To review the literature on the effects of periodization for those looking to improve muscle size and strength. Design and Methods: Non-systematic review. Research articles were collected using search terms such as linear periodization, non-linear periodization, non-periodized, undulating periodization, and strength training models. Results: Previous research has found no differences in muscle size between periodized and non-periodized training programs. Further, there are conflicting reports on what periodized program is superior for increasing muscle strength. It is our contention that the proposed superiority in strength with periodized programs is often explained by the principle of specificity. Conclusion: The use of a periodized program may be advantageous for an athlete in certain sports due to practice and competi tions throughout the season. However, we wish to suggest that the proposed benefits of periodization for those only interested in increasing muscle size and strength are largely founded in conjecture and that there is little compelling evidence that periodization is a superior method of training.